How Were Experiences of Stoma for Nursing Students? - Vural, Fatma; Durmaz Edeer, Aylin; Yasak, Kübra; Kaplan, Ali; Özbayır, Türkan; Karaveli Çakır, Selda (Galenos Yayinevi, 2021)
Aim: The purpose of this study was to determine the experiences of baccalaureate nursing students with stoma bags and adaptors over 24 hours. Method: The study was semi-experimental. Participants included 80 students from two nursing faculties with 10 students per class. The students were chosen by random sampling. Stoma adaptors were worn as a pouch and removed after 24 hours. A data collection form was used to gather the students’ demographic and descriptive characteristics, previous degree of knowledge and experience about stomas, and experiences and feelings they had during the process. In the data analysis, percentages and the chi-square test were used. Results: Among the students, 86.3% stated they worried continuously that the stoma bag would leak and 30.0% stated they were anxious because of the stoma. Four main themes emerged from the answers: (1) restriction in social activities, (2) restriction in physical activities, (3) worry about a stoma leakage, and (4) effect on body image. All of the students said that they understood better how stoma patients felt and that it was a good experience for them. Conclusion: These experiences and feelings are important for baccalau reate nursing students to have more awareness about living with a stoma.
Keywords: 4. Education